Review on the teaching of programming and computational thinking in the world - Belmar, Héctor (Frontiers in Computer Science, 2022)
Recent studies suggest that computational thinking, composed of the skills of abstraction, decomposition, algorithmization, debugging and problem solving, is the fundamental skill for scientific, technological, and economic development for the 21st century. However, this diagnosis that is unveiled in rich countries remains nebulous for poor countries. The problem is that education in computational thinking is fundamental for countries to insert themselves in the international arena in an advantageous way and thus achieve the welfare goals for the population of each country. The objective of this research is to make a bibliographic review that shows the state of the art in the teaching of computer programming and computational thinking in the 5 continents. In the review, the advances in the countries of Europe, North America, Oceania, and Asia were observed, while in Latin America and Africa, the advances are still basic in some countries and nonexistent in others. This review is based on Kitchenham's method applied to software engineering. The main search terms were "Computational thinking" and "Teaching computer programming". The search was performed in the ACM, Conference on Computational Thinking Education (Hong-Kong), Google Scholar, WOS and SCOPUS databases, from October until December 2020, whose publication year was from 2016 onwards. One of the main results found is that the teaching of computational thinking in England was implemented in schools in 2014; in Germany, it has been implemented since 2016 at a transversal level in universities; in South Korea, China, and Taiwan it has been implemented since 2016. However, in Latin America and Africa governments, the subject is still not considered.